Effects of geographical, soil and climatic factors on the two marker secondary metabolites contents in the roots of Rubia cordifolia L. - Wang, Yanlin; Liu, Huanchu; Yu, Shuai; Zhang, Yue; Huang, Yanqing; He, Xingyuan; Chen, Wei (Frontiers in Plant Science, 2024)
The growth and quality of medicinal plants depend heavily on environmental variables. The quality of Rubia cordifolia, an important medicinal plant, is determined by the two main secondary metabolites of the root, purpurin and mollugin. However, their relationship with environmental factors has not been studied. In this study, the purpurin and mollugin contents of R. cordifolia roots from different sampling sites in China were measured using ultra-high-performance liquid chromatography, and the correlations between the two secondary metabolites and environmental variables were analyzed. The results showed that there were significant differences in the contents of purpurin and mollugin in the roots of R. cordifolia at different sampling points. The content of purpurin ranged from 0.00 to 3.03 mg g -1 , while the content of mollugin ranged from 0.03 to 10.09 mg g -1 . The quality of R. cordifolia in Shanxi, Shaanxi and Henan border areas and southeastern Liaoning was higher. Liaoning is expected to become a R. cordifolia planting area in Northeast China. Correlation and regression analysis revealed that the two secondary metabolites were affected by different environmental factors, the two secondary metabolites contents were positively correlated with longitude and latitude, and negatively correlated with soil nutrients. In addition, higher temperature and shorter sunshine duration facilitated the synthesis of purpurin. Annual precipitation might be the main factor limiting the quality of R. cordifolia because it had opposite effects on the synthesis of two major secondary metabolites. Therefore, this study is of great significance for the selection of R. cordifolia planting areas and the improvement of field planting quality.